Transforming Mosque Financial Management: Utaut Insights into E-Payment Readiness - Idris, Junainah; Atan, Nur Syaheera; Nor, Fadilah Mat; Ariffin, Nur Ifwah (SCAD Independent, 2024)
This paper aims to summarize studies on the Unified Theory of Acceptance and Use of Technology (UTAUT) in e-payment readiness and identify the research gap. The study used a systematic literature review method. A total of 33 articles on UTAUT were published over the past five years, from 2019 to 2023. The 33 articles were the subject of the study. The data were collected by studying documentation of several previous articles through database searches such as Web of Science and Scopus. The data analysis techniques were quantitative (statistical) and qualitative (descriptive). This study indicated that 33 articles highlighted UTAUT in e-payment readiness, demonstrating that there is still a lack of studies involving e-payments at mosque institutions, especially among management groups. The findings will provide mosque authorities with a comprehensive overview of mosque financial digitalization for more relevant and efficient fund collection methods.